Production and marketing of pecan nuts (Carya illinoensis Koch) in northern Coahuila, Mexico - Orona Castillo, Ignacio; Sangerman-Jarquín Dora Ma.; Fortis Hernández Manuel; Vázquez Vázquez Cirilo; Gallegos Robles Miguel Ángel (Revista Mexicana de Ciencias Agrícolas, 2018)
Pecan nut cultivation in Mexico is a growing activity, especially in northern states, due to the climatic and edaphological adaptation of pecan trees, as well as market conditions and the attractive returns from selling pecan nuts to the USA. In the state of Coahuila, which borders the USA and is the center of the region from which the pecan tree originated, there are 13 thousand hectares planted with pecan trees distributed throughout the state; the purpose of this study was to characterize the production , marketing and value addition processes of pecan nuts in the northern part of the state (five springs region), in order to identify areas of opportunity that the actors involved can take advantage of for obtaining better benefits. Two surveys were done during the period 2006- 2007 with open and closed questions; one was applied to producers and the other to marketers-processors. The results clarified the marketing channels and the product sales margins, leading to the conclusion that it is necessary to improve technically the assistance to producers, to improve also the presentation of the product prior to marketing, and to support the processing of the nut in order to improve the performance of this production system.